Multiple Myeloma: Emerging Therapies, Diagnostic Techniques - Kuznar, Wayne (MD Conference Express, 2013)
An improved understanding of the biology of multiple myeloma (MM) and the identification of new drugs have improved the therapeutic approach. Myeloma consists of at least seven subtypes based on cytogenetics and molecular features. This article discusses the use of autologous stem cell transplant as a therapy for MM, approaches to patients with ‘double-refractory’ myeloma, and advances in diagnostic assays and monitoring of MM.